THE INFLUENCE OF STORE ATMOSPHERE AND VIRAL MARKETING ON BUYING DECISION: (Study on Seis Café & Public Space Consumers on Sei Silau Street, Medan City) - Farhan, Muhammad Rafdy; Adlina, Hafiza (Transpublika Publisher, 2022)
This study aims to analyze the influence of Store Atmosphere on Buying Decisions on Seis Café & Public Space consumers, analyze the effect of Viral Marketing on Buying Decisions on Seis Café & Public Space consumers, analyze the influence of Store Atmosphere and Viral Marketing on Buying Decisions on Seis Café & Public Space consumers. The research method used in this research is quantitative approach. The population in this study was Seis Café & Public Space consumers, the sample set was 100 consumers (respondents) with a sampling technique using purposive sampling. Data collection techniques in this study used primary data obtained from distributing questionnaires google form, for secondary data obtained through books and articles related to this study. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear analysis, partial test, simultaneous test and determination test. The results of the research conducted indicate that the Store Atmosphere (X1) and Viral Marketing (X2) variables have a significant effect on Buying Decisions (Y). Store Atmosphere and Viral Marketing variables simultaneously affect Buying Decisions (Y). The coefficient of determination test shows that there is a very close relationship between Store Atmosphere and Viral Marketing, towards Buying Decisions with an R value of 0.797 through an adjusted R square value, it is revealed that Store Atmosphere and Viral Marketing variables contribute 63.8%, to Buying Decisions, while 36,2% is influenced by other variables beyond the study.